Outcomes and complications in superior semicircular canal dehiscence surgery: A systematic review. (15th September 2015) - Gioacchini, Federico Maria; Alicandri‐Ciufelli, Matteo; Kaleci, Shaniko; Scarpa, Alfonso; Cassandro, Ettore; Re, Massimo
Abstract : Objective: Superior semicircular canal dehiscence (SSCD) represents a rare condition that may be associated to some particular symptoms as vertigo, autophony, and Tullio phenomenon. In those patients who present severe symptoms surgical treatment is required. Middle fossa craniotomy and transmastoid approaches are both described. Concerning repairing techniques, plugging and/or resurfacing are typically used to close the defect. Our aim was first to analyze the overall outcomes and complications of this surgery. Our second aim was to make a comparison between the different surgical modalities to investigate the eventual advantages and disadvantages. Review Methods: A search through Ovid MEDLINE was organized in January 2015 to include all eligible articles. A statistical analysis of the obtained data was performed. Results: Twenty studies comprising a total of 150 procedures were included. Four modalities of canal repair were described (plugging, capping, resurfacing, plugging with resurfacing). The overall rate of success resulted in 94% (95% confidence interval: 87%‐97%). No statistically significant differences were observed among the different modalities of canal repair concerning both success rate and surgical complications. Differences observed between the middle fossa approach and transmastoid approach in terms of outcome were not statistically significant. Conclusions: This review showed that surgical treatment for SSCD represents a safe option for those patients with severe symptoms of this condition. Differences observed in terms of success rate or complications were analyzed between the different surgical techniques with results that were not statistically significant. Level of Evidence: NA Laryngoscope, 126:1218–1224, 2016